The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
Multi-, Inter- And Transdisciplinary Research in Landscape Archaeology 2016
DOI: 10.5463/lac.2014.32
|View full text |Cite
|
Sign up to set email alerts
|

New Approaches in Landscape Analysis of the Bronze Age in Central-Western Sardinia: the Area of Mogoro (Oristano – Italy)

Abstract: Research on the prehistoric and proto-historic landscape in Sardinia (Italy) allows knowledge and analysis of the island's archaeological heritage. Besides, recent studies have aimed to delineate the type of relationship that the prehistoric and proto-historic societies established with the variegated Sardinian landscape in connection with the ways of articulation and territorial appropriation, without neglecting the important and fundamental aspect of economic organisation of the territory. From this point of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 1 publication
0
3
0
1
Order By: Relevance
“…In this territory, currently we know at least 29 sites (Cicilloni et al, 2015e) belonging to the Protohistoric period: 1 archaic nuraghe, 9 simple towers, 17 complex nuraghi, 1 giants' tomb, 1 sacred well (fig. 2).…”
Section: Mogoro Sample-area (Central-western Sardinia)mentioning
confidence: 99%
See 1 more Smart Citation
“…In this territory, currently we know at least 29 sites (Cicilloni et al, 2015e) belonging to the Protohistoric period: 1 archaic nuraghe, 9 simple towers, 17 complex nuraghi, 1 giants' tomb, 1 sacred well (fig. 2).…”
Section: Mogoro Sample-area (Central-western Sardinia)mentioning
confidence: 99%
“…4) (Cabras, 2015). During the phases of the Middle and Late Bronze Age this part of Sardinia shows a widespread distribution that denotes a systematic control of the territory (Cabras, 2015;Cicilloni et al, 2014;Cicilloni et al, 2016a;, and the creation of a specific landscape in which visual connection an monumental buildings played a complementary role of exhibition and visual domain.…”
Section: Mogoro Sample-area (Central-western Sardinia)mentioning
confidence: 99%
“…More recent research in the Mogoro territory, coupled with some archaeobotanical analyses, revealed an intense exploitation of the land, with areas used for agricultural activities, especially for the cultivation of cereals (Cabras, 2015;Cicilloni et al, 2016;Cicilloni et al, 2017).…”
Section: Excavation In Nuraghe Cuccurada-mogoro: Stratigraphy and Groundstone Toolsmentioning
confidence: 99%
“…De ser cierta tal interpretación, la representación tiene, de nuevo, puntos en común con otras como la de Orri y la de Su Crabiosu. En cualquier caso, los círculos concéntricos son representaciones frecuentes y se constatan también en domus de janas (Tomba delle Spirali, Ossi) (Tanda, 1977:363) y sobre determinados megalitos (Merella, 2009) cuya cronología, según algunos hallazgos como los de Motorra (Dorgali) (Cicilloni, 2009) puede remontarse a la cultura Ozieri. También se conocen petroglifos con este tipo de representaciones de círculos concéntricos, aunque ciertos ejemplos como el de Pirarba (Barisardo) muestran un mayor cuidado en el diseño (con mayor regularidad y generando espirales en lugar de círculos concéntricos) y en el número de círculos que rodean el punto central que en el caso del motivo de mayores dimensiones es constituido por una cazoleta excavada, estando presentes otras cazoletas tanto al interior de espirales como fuera de ellas (Merella, 2009:140-141).…”
Section: -Las Pinturas Rupestres De Luzzanas En El Contexto De Las De...unclassified